The fine art of IC design. - Chappell, B.
Designers of 100-million-transistor chips face daunting challenges, most especially in dealing with switching currents, optimization, asynchronization, reuse, and design skills. Certain subjects-interconnections, for example-will prove to cut across all five topics. All the same, the issues offer a useful view on what designers will face in handling these complexities. These five topics are discussed in the paper
Keywords: 100-million-transistor chips; IC design; Asynchronization; Design skills; Interconnections; Optimization; Reuse; Switching currents